A Handbook of Theological Terms Their meaning and backgoround exposed in over 300 articles - Harvey, Van A. (New York Simon & Schuster, 1997)
A growing number of nonprofessional readers of theology, whether as individuals, in study groups, or in college courses, treat religion as the subject of disciplined study. Some acquaintance with the technical and traditional vocabulary is an asset to t
Keywords: Theology -- Dictionaries. Theology